Purification, crystallization and preliminary X-ray diffraction analysis of crotamine, a myotoxic polypeptide from the Brazilian snake Crotalus durissus terrificus - Coronado, Monika A. [UNESP]; Georgieva, Dessislava; Buck, Friedrich; Gabdoulkhakov, Azat H.; Ullah, Anwar [UNESP]; Spencer, Patrick J.; Arni, Raghuvir K. [UNESP]; Betzel, Christian (Wiley-Blackwell, 2012)
Crotamine, a highly basic myotoxic polypeptide (molecular mass 4881 Da) isolated from the venom of the Brazilian rattlesnake Crotalus durissus terrificus, causes skeletal muscle contraction and spasms, affects the functioning of voltage-sensitive sodium channels by inducing sodium influx and possesses antitumour activity, suggesting potential pharmaceutical applications. Crotamine was purified from C. durissus terrificus venom; the crystals diffracted to 1.9 angstrom resolution and belonged to the orthorhombic space group I212121 or I222, with unit-cell parameters a = 67.75, b = 74.4, c = 81.01 angstrom. The self-rotation function indicated that the asymmetric unit contained three molecules. However, structure determination by molecular replacement using NMR-determined coordinates was unsuccessful and a search for potential derivatives has been initiated.
Keywords: crotamine; myotoxins; Crotalus durissus terrificus